Recent Trends in Morphology-Controlled Synthesis and Application of Mesoporous Silica Nanoparticles - Nabanita Pal; Jun-Hyeok Lee; Eun-Bum Cho (Nanomaterials, 2020)
The outstanding journey towards the investigation of mesoporous materials commences with the discovery of high surface area porous silica materials, named MCM-41 (Mobil Composition of Matter-41) according to the inventors’ name Mobile scientists in the United States. Based on a self-assembled supramolecular templating mechanism, the synthesis of mesoporous silica has extended to wide varieties of silica categories along with versatile applications of all these types in many fields. These silica families have some extraordinary structural features, like highly tunable nanoscale sized pore diameter, good Brunauer–Emmett–Teller (BET) surface areas, good flexibility to accommodate different organic and inorganic functional groups, metals etc., onto their surface. As a consequence, thousands of scientists and researchers throughout the world have reported numerous silica materials in the form of published articles, communication, reviews, etc. Beside this, attention is also given to the morphology-oriented synthesis of silica nanoparticles and their significant effects on the emerging fields of study like catalysis, energy applications, sensing, environmental, and biomedical research. This review highlights a consolidated overview of those morphology-based mesoporous silica particles, emphasizing their syntheses and potential role in many promising fields of research.